UCHKUS: A INCA SETTLEMENT IN HUANCAVELICA - Ruiz Estrada, Arturo (1998)
The Inca administration on the archaeological settlement of Uchkus, and the degree of impact of the Inca style in the architectural planning and local pottery are analyzed in this paper.